A model of Islamic tourism towards religious motivation and tourist satisfaction in Malaysia - Haque, A. K. M. Ahasanul; Momen, Abdul (Springer Singapore, 2017)
Abstract The aim of this chapter is to explore the roles of religious motivation in the relationship between tourists' antecedents and their destination and satisfaction , and to provide some guidelines to aid tourism professionals in developing and implementing the niche strategy of Islamic tourism for the advancement of the tourism industry of a country such as Malaysia. In the Malaysian context, the religious motivation of international Muslim tourists is increasingly active in their minds, which suggests that tourism professionals consider Shariah-compliant tourism to keep long-term customer relationships. Perceived value, destination image, and service quality influence international Muslim tourists to look to this destination for satisfaction . As a moderation role, the more the level of religious motivation varies, the more the effect of moderator yields. In addition, tourism professionals necessarily require understanding relevant Shariah rules, character istics of international Muslim tourists , and the context of the Islamic country so that they can design a Shariah-compliant tourism strategy and policy effective for further growth of the tourism industry